Optimization of the residual bending flexure of round polymer plate with glass transition at non-uniform cooling - Smetannikov, Oleg Yur'evich (Computational Continuum Mechanics, 2010)
The problem of minimization of the residual displacements in the round epoxy resin ED-20 plate by additional force loading is solved. For the description of thermomechanical behaviour of a material with relaxation transition the model developed earlier is used. The technique of superposition of step-by-step thermoelasticity problems solving, realized in ANSYS program, is used at numerical calculations. It is shown, that additional restriction allows to lower considerably a level of operating loading and to increase reasonableness of a problem.
Keywords: vitrification; numerical methods; technological stresses; residual stresses; finite element method; optimization